Peningkatan Kesadaran Kebersihan Melalui Game “Habertan” Pada Siswa Siswi Pesantren Muhyiddin Gebang Putih, Sukolilo, Surabaya - Sudaryanto, Aris; Fathoni, Kholid; Hakkun, Rizky Yuniar; Revindasari, Fony; Safrodin, Mohamad; Nurindiyani, Artiarini Kusuma; Damastuti, Fardani Annisa; Sa’dyah, Halimatus; Zikky, Mohamad; Akbar, Zulhaydar Fairozal; Darmawan, Zakha Maisat Eka; Dianta, Ashafidz Fauzan; Hapsari, Veronica Lita (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2024)
Environmental cleanliness is an important aspect of life because if it is dirty it will become a breeding ground for disease and flooding. Gebang Putih and Keputih are areas prone to dengue fever and flooding in Surabaya. Therefore, the community service provides socialization of cleanliness to children with this Habertan Game. The game was chosen because it has been proven to influence human behavior. However, Habertan is designed to have a positive effect in the form of increasing awareness of environmental cleanliness. The participants of the activity were 30 students of Madrasah Pesantren Muhyiddin. This activity is expected to increase the knowledge and awareness of participants in waste management. Impact measurement was carried out by giving participants questions before and after the activity. Based on the data obtained, it was proven that 76.6% of participants experienced an increase in knowledge about waste management after participating in the socialization.